A Quality control study on Cosmos Bottling Corporation - Calayag, Laura N.; Mosqueda, Maria Melissa E.; Redillas, Joshua E. (Diliman, Quezon City College of Engineering, 1999)
Cosmos Bottling Corporation is the only locally based manufacturer of bottled softdrinks in the country today. The plant understudy located at San Pedro, Laguna, is the first provincial plant of Cosmos, aimed to meet the continuing demand of consumers from bottled softdrinks outside Metro Manila. The group was limited to study the Line 2 Production, which bottles the 800 mL Pop Mega, and which includes the following processes; uncasing, pre-inspection, washing, empty-bottle inspection, filling, crowning, final product inspection and the case packing. The quality control department handles three quality activities, namely, concentration monitoring, fill height determination and after-washing inspection. The group was able to identify two problems, breakages and rejects (in terms of fill height), believed to be the reason for the company?s low productivity. It was found out that the percentage of the total breakages to that of the total monthly production is greater than the allowable percentage set by the management. Breakages rate is proportional to production volume. The larger the volumes of production, the bigger are the chances that breakages will occur. The major cause of bottle breakage is the poor quality of the bottles that enter production. Unbearable pressure, temperature and collision with other bottles when going through the whole process are some of its causes. Since pressure and temperature are constantly set at 30 psi and 130 degrees-170 degrees Fahrenheit, respectively, for the wager and, 60 psi and 200 degrees F, respectively for the filler machine, recommendation to reduce collision of bottles was made. Reducing the number of incoming bottles will reduce contact stress, minimizing the deterioration of the bottle?s quality. Rejects, on the other hand, in terms of fill height can be accounted to the filling process. The correct fill height is set by the management at 59 mm with an allowable deviation of ± 3 mm, that is, between 56 mm to 62 mm. Samples were taken and deviations from the permissible range was recorded and plotted on the control charts. It was seen that the process is out-of-control or unstable. There were 2 recommendations made for this problem, one for the machine and another for the finished product inspectors. For the machine it was recommended that the management test the nozzles of the filler machine regarding its reliability. For the inspector, it was recommended that the management provide reference lines for the fill height so that accuracy in inspecting is assured.
Feasibility study
Submitted in partial fulfillment of the course requirements in IE 135 : Industrial Quality Control
Keywords: Cosmos Bottling Corporation; Bottle industry; Quality control